Determination of Physical and Chemical Properties of Honey from the Mountainous and Lowland Regions of Kyrgyzstan - K. Kadyrova; J. Smanalieva (MANAS: Journal of Engineering)
The purpose of the study is to determine the basic physical and chemical properties of honey collected from the mountainous and lowland regions of Kyrgyzstan. Honey samples from Suusamyr, Sary-Chelek,Toktogul, Issyk-Kul, Talas , Chon-Kemin and Uzgen (Kara-Shoro) were chosen as subjects of the study. The results show that certain chemical parameters such as mass fraction of water, reducing sugar, total acidity and pH of the honey samples are within the limits established by normative documents. Diastase number of test samples have shown good results. The maximum diastase number was found in the Toktogul and Suusamyr honey (38.97 ±20 and 33.73± 18 Schade units accordingly) collected from mountain regions and this demonstrates high quality and benefits of mountain honey.